STRATIFIED FLOW OF GAS-LIQUID MIXTURE IN HORIZONTAL PIPES - Avlakulov, Abdimazhit; Babajanova, Iroda; Babajanov, Yuldosh (Innovatsion texnologiyalar, 2024)
Research in the field of hydrodynamic calculations of the flow of gas-liquid mixtures in pipelines has been carried out by many researchers. They theoretically and experimentally studied various hydraulic and hydrodynamic features of gas-liquid flows. However, in these works the obtained parameters have an error associated with a large number of variables characterizing the two-phase flow. Therefore, this article sets a goal aimed at a mathematical description of the calculated dependencies for a stratified flow structure in a pipeline. In this case, the objectives of the work are to determine the calculated parameters of two-phase flows and pressure loss in horizontal pipelines or with relatively small values of the angle of inclination with a stratified flow structure. For the hydraulic calculation of downward flows with an angle of inclination a from 10 to 100 , we used the formulas of Altschul and the Research Institute of Gas, and equations for the main parameters of the pipe when stratified gas-liquid mixtures passed through it were derived